Chronic Lung Allograft Dysfunction: A Systematic Review of Mechanisms. Issue 9 (September 2016) - Royer, Pierre-Joseph; Olivera-Botello, Gustavo; Koutsokera, Angela; Aubert, John-David; Bernasconi, Eric; Tissot, Adrien; Pison, Christophe; Nicod, Laurent; Boissel, Jean-Pierre; Magnan, Antoine
Abstract : Abstract: Chronic lung allograft dysfunction (CLAD) is the major limitation of long-term survival after lung transplantation. Chronic lung allograft dysfunction manifests as bronchiolitis obliterans syndrome or the recently described restrictive allograft syndrome. Although numerous risk factors have been identified so far, the physiopathological mechanisms of CLAD remain poorly understood. We investigate here the immune mechanisms involved in the development of CLAD after lung transplantation. We explore the innate or adaptive immune reactions induced by the allograft itself or by the environment and how they lead to allograft dysfunction. Because current literature suggests bronchiolitis obliterans syndrome and restrictive allograft syndrome as 2 distinct entities, we focus on the specific factors behind one or the other syndromes. Chronic lung allograft dysfunction is a multifactorial disease that remains irreversible and unpredictable so far. We thus finally discuss the potential of systems-biology approach to predict its occurrence and to better understand its underlying mechanisms. Abstract : Royer et al review the immune mechanisms involved in the development chronic lung allograft dysfunction (CLAD), which manifests as bronchiolitis obliterans syndrome (BOS) or restrictive allograft syndrome (RAS), concluding that CLAD is a multifactorial disease that remains irreversible and unpredictable.